The Influence of the Work Environment and Work Discipline in Improving Employee Performance at the Makassar Maritime Science Polytechnic - Aisyah Nur Ramadhini; M. Hidayat; Irwan Abdullah (GoodWill, 2026)
This research is a type of quantitative research with the aim of determining the influence of the work environment and work discipline in improving employee performance at the Makassar Maritime Science Polytechnic. The sample for this research was taken from employees who worked at the Makassar Maritime Science Polytechnic. The type of data used is quantitative data obtained through distributed questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include primary data and secondary data. The research instrument uses the Likert scale method. Based on the results of data analysis using multiple linear regression using the Statistical Package for the Social Science (SPSS) version 26 application. The results of this research show that the work environment does not have a significant effect on improving employee performance and work discipline has a significant effect on improving employee performance. Simultaneously, work environment variables and work discipline have a significant effect on improving employee performance at the Makassar Maritime Science Polytechnic.